The Impact of Good Corporate Governance To Financial Performance - Winarsih; Athoillah (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2021)
Background: Corporate governance plays an important role in the company because it can reflect how the performance in the company, especially financial performance. Financial performance is one proof of how the results or profits obtained by the company. To show optimal financial performance, it is influenced by Management Efficiency and Corporate Capital Structure, both of which are also important components in improving financial performance. Purpose: The purpose of this article is to find out more about the influence of Good Corporate Governance on Financial Performance. Methods: The sampling in this study is approximately 30 manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2018. The number of samples was obtained based on the type of simple experimental research. Conclusion: This research produces a conceptual framework which focuses on improving financial performance through good corporate governance which is also influenced by management efficiency and corporate capital structure.